BENTUK DAN MAKNA KATA DALAM SYAIR ABDUL MULUK KARYA RAJA ALI HAJI - Islamidina Z Islamidina Z; Elmustian Elmustian; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study titled the form and meaning of the word in syair Abdul Muluk by Raja Ali Haji. The reason why researchers chose the form and meaning of the word as a research study because many words are difficult to understand for researchers as lay people. Apart from that, not everyone can understand the form and meaning of the word or language presented in the poem. Moreover, today the rapid development of technology and communication is such that old literary works are abandoned and can be considered almost extinct. This research is a descriptive qualitative research that describes and describes the results of research that have found various forms of words, namely, primitives, connected forms, repeating forms, lexem alloys, and compound forms. The words identified by the author number 1514 words. The results of the identification of 1514 words are the basic forms with 767 words. Word form, which also appears a lot, is the form of the number of 663 words, then the repetition form is 65 words, lexem alloys are 15 words and the compound form is 4 words. The meanings examined in this study are lexical meanings, grammatical meanings, text meanings, and idiomic meanings.Key Words: form, meaning, word, poem